Morals in Everyday Exemplary Behavior: Phenomenology of Teacher-Student Collaboration in Elementary Schools - Samugara, Bisma; Hakim, Faisol; Asnawan, Asnawan (Thawalib: Jurnal Kependidikan Islam, 2026)
Moral education at Sekolah Dasar Negeri Kencong 01 is crucial for character development; however, limited time for Islamic Religious Education and the heterogeneity of students' characters hinder the effectiveness of teacher-student collaboration. This study aims to explore the meaning of collaborative experiences between teachers and students in moral development through character education practices at Sekolah Dasar Negeri Kencong 01. Using a qualitative phenomenological approach, the research examines the essence of these experiences and validates data through triangulation to ensure credibility. The results show that student moral formation occurs holistically through the habituation of daily values, teacher role models as moral exemplars, participatory collaborative practices, and the integration of religious activities. Success is influenced by the synergy between school and family, as well as the dynamics of supporting and limiting factors, such as learning time constraints and diverse student characteristics. Effective collaboration strengthens value internalization, making moral education not merely normative or cognitive, but deeply internalized through concrete experiences and consistent interactive relationships. In conclusion, student morality is shaped through teacher-student collaboration, modeling, and the integration of values into daily life. This study highlights the importance of real-life experiences, teacher exemplars, and school-family collaboration in fostering student moral development.